World Heritage at 50: policy and practice – key achievements and major challenges - Rössler, Mechtild (Protection of Cultural Heritage, 2023)
The 1972 World Heritage Convention is the most universal legal instrument in heritage conservation with 194 States Parties, more than 1000 natural and cultural heritage sites protected for their Outstanding Universal Value and a well-established system of monitoring and reporting. It is therefore a great pleasure for me to celebrate the achievements of this unique Convention with stakeholders. At the same time a number of challenges in terms of policy and practice have to be discussed and addressed and I will share with you my reflections of 30 years working within the World Heritage system. This is also unique and brings to you a specific lens through the viewpoint from the UNESCO Secretariat but also as researcher on the UNESCO and World Heritage history of the past decades.